2017
DOI: 10.1101/128777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Like Sugar in Milk”: Reconstructing the genetic history of the Parsi population

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In our search of the SNPs reported to be associated with high risk by Zeberg & Pääbo 6 , we found rs10490770 from genome-wide datasets 14,15,[18][19][20] . We applied the same tests done for the ACE2 SNPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our search of the SNPs reported to be associated with high risk by Zeberg & Pääbo 6 , we found rs10490770 from genome-wide datasets 14,15,[18][19][20] . We applied the same tests done for the ACE2 SNPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we searched the genotype datasets generated by this platform. The frequency data for both of the SNPs from various Indian populations were extracted by using Plink 1.9 11 , from 1000 genome project data phase 3 12 data published by the Estonian Biocentre [13][14][15][16] and our newly genotyped samples for various Indian states and Bangladesh (Supplementary Table 1). In addition to our previous study 10 , more samples were added for the SNP rs2285666.…”
Section: Methodsmentioning
confidence: 99%
“…South West coastal India is a region of high population diversity and with complex genetic history. Some earlier studies with groups like Jews (Behar, et al 2008; Behar, et al 2010; Chaubey, et al 2016), Parsees (Chaubey, et al 2017) and Roman catholic (Kumar, et al 2021) already pointed out the complex genetic history and multilayered genetic structure of populations in this region. Also, earlier studies (Moorjani, et al 2013; Narasimhan, et al 2019) indeed suggested about the multi layered admixture in the Indian subcontinent specially among caste groups.…”
Section: Discussionmentioning
confidence: 98%
“…Reason we proposed behind this was the complex nature of admixture history in the form of multiple layers of ancestries. More specifically in South West coast of India, studies with some unique population groups like Jews, Parsees and Roman Catholics have already pointed about the additional layers of admixture among them (Chaubey, et al 2016; Chaubey, et al 2017; Kumar, et al 2021). Previous genetic studies based on Y chromosomal microsatellite markers also found more west Eurasian or North West Indian genetic influence in gene pool of Nairs and Ezhava (Nair, et al 2011; Mahal and Matsoukas 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained a total of 5 SNPs (rs2070788, rs734056, rs12329760, rs2276205, and rs3787950) was observed in our data and studied subsequently in detail. Data from the Estonian Biocentre (42)(43)(44)(45), data from phase 3 of the 1,000 Genomes Project (46), and our new genotyped samples from several Indian states were used to calculate the frequency of each of these SNPs among various Indian populations using plink 1.9. State-wise frequency maps for rs2070788 and COVID-19 CFR among the Indian population were made by https://www.datawrapper.de/.…”
Section: Methodsmentioning
confidence: 99%